Evaluating the Use of Project Based Teaching on the Science Laboratory Course According to the Views of the Classroom Teacher Candidates - Gamze Karaer; Ersin Karademir; Özden Tezel (Anı Publishing, 2020)
This study is to aim that evaluating of the project based instruction (PBI) activities effects on science laboratory course depending on the pre-service classroom teachers' opinions. This study was designed with the case study and 36 pre-service classroom teachers participated. The data was collected via "interview form towards science laboratory applications" Interviews were carried out two times before and after instruction. Qualitative data were analyzed by content analysis. Findings indicated that depending on pre-service classroom teachers' opinions PBI teaching method enriched science laboratory activities and increased their science laboratory attitudes and self-efficacy beliefs. Throughout the process, pre-service teachers learned how the project based instruction process conducted and their teaching strategies. Depending on these results, science-teaching process apart from science laboratory activities can be enriched by PBI method.